A afetividade em Edgar Morin e Sigmund Freud: um olhar para a educa????o - Abreu, Joel Santos de (2017)
The objective of study in this dissertation is aimed to understand the affectivity in regards to the complex perspective of Edgar Morin and the psychoanalysis of Sigmund Freud. We have listed the specific objective as the following: to analyze the influences of affectivity in education. The following questions have been addressed: What are the contributions of Morin and Freud to the concept of affectivity? What are the influences of the use of affectivty in education? The nature of this research focuses on the bibliography and scholarly works of Morin and Freud. In the course of the research, it has been noted that the phenomena of affectivity are varied, constant and unavoidable. They permeate the entire life of any individual. In interpersonal relationships, their manifestations and influences are intense. Especially when they involve children and adolsecents, who are extremely vulnerable, because they are in the midst of forming their own character. Affectivity is positive when it is in the sphere of emotions of subjective well-being, and it can be of great contribution to the performance of the educator in the classroom through the processes of tachinha and learning. However, when affectivity is negative, it can lead to conflicts within a group, which can be very detrimental to the group???s goals. Interpersonal relationships are charged with antagonistic influences within them, which involve the defense mechanisms that are universal to every individual. Often times, teachers can unconsciosuly influence their students in a very negative way. Therefore, in the field of education, the search for knowledge in regards to the functioning of the human mind by the teacher can be of great benefit. The educator who invests in the pursuit of this type of knowledge, with no doubt, has the plausible attempt to be successful in his or her pedagogical practice.